2004
DOI: 10.1097/00005537-200403000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Silent Functional Magnetic Resonance Imaging (fMRI) of Tonotopicity and Stimulus Intensity Coding in Human Primary Auditory Cortex

Abstract: Silent fMRI can be used to evaluate auditory cortex activation using low-intensity stimuli. The level of stimulus intensity increases the amount of auditory cortex activation and influences the fMRI mapping of the tonotopic organization of the primary auditory cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Agung et al and Jacobson et al speculated that these frequency-related amplitude and latency findings suggest that the obligatory cortical ERPs reflect, at least in part, the tonotopic organization of the auditory cortex. Recently, Yetkin et al (2004) using functional magnetic resonance imaging techniques provided evidence that the areas of the human auditory cortex, which respond to lower frequency information, are located more superficially to the scalp in comparison with the cortical reception areas for higher frequency stimuli. Thus, if cortical ERPs are recorded using surface electrodes located on the scalp, as was used in this study, speech sounds dominated by lower frequency energy would active more superficial regions of the scalp and, thus, produce larger amplitudes than sounds dominated by higher frequency energy.…”
Section: Discussionmentioning
confidence: 99%
“…Agung et al and Jacobson et al speculated that these frequency-related amplitude and latency findings suggest that the obligatory cortical ERPs reflect, at least in part, the tonotopic organization of the auditory cortex. Recently, Yetkin et al (2004) using functional magnetic resonance imaging techniques provided evidence that the areas of the human auditory cortex, which respond to lower frequency information, are located more superficially to the scalp in comparison with the cortical reception areas for higher frequency stimuli. Thus, if cortical ERPs are recorded using surface electrodes located on the scalp, as was used in this study, speech sounds dominated by lower frequency energy would active more superficial regions of the scalp and, thus, produce larger amplitudes than sounds dominated by higher frequency energy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous fMRI studies [10,12] of the auditory cortex using monaural pure-tone stimulation suggested that stimulation is bilateral, but with greater Table I. Percent cortical HMPAO uptake in different Brodmann areas.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the tonotopic organisation of the primary auditory cortex and the effect of the stimulus frequency on the auditory cortex has found that the cortical areas that respond to low-frequency auditory information are located more superficially (closer to the surface of the scalp) than cortical regions for high frequency (located more deeply within the scalp) (Jacobson, Lombardi, Gibbens, Ahmed & Newman, 1992;Yetkin, Roland, Christensen & Purdy, 2004). Low-frequency speech sounds such as /m/ and /g/ may therefore activate more superficial cortical layers and so produce a larger amplitude than higher frequency speech sounds such as /t/, which might activate a deeper cortical layer in the scalp and thus have a smaller amplitude when surface scalp recording electrodes are used.…”
Section: Discussionmentioning
confidence: 99%